1995
DOI: 10.1016/s0022-5347(01)67231-8
|View full text |Cite
|
Sign up to set email alerts
|

Sono-Urethrography in the Evaluation of Anterior Urethral Strictures

Abstract: During a 7-year period 123 paired urethrographic and sono-urethrographic studies were performed on 101 patients with 110 urethral strictures. In all but 3 cases the urethra was subsequently evaluated either cystoscopically or at open operation. Sono-urethrography readily identified urethral calculi, diverticula and false passages. It correctly identified the stricture and its site in every case. There was a significant difference between stricture length as measured by urethrography compared to that measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 5 publications
2
31
0
2
Order By: Relevance
“…Urethral sonography is unreliable in diagnosing the depth of spongiofibrosis in comparison with histopathological correlation. 16 In the present study, BMG dorsal onlay urethroplasty and BMG dorsal Inlay urethroplasty provided comparable outcomes for anterior urethral strictures repair. We reported a success rate of 88% in the dorsal onlay group, whereas the success rate in the dorsal inlay group was 86.4%.…”
Section: Discussionsupporting
confidence: 55%
“…Urethral sonography is unreliable in diagnosing the depth of spongiofibrosis in comparison with histopathological correlation. 16 In the present study, BMG dorsal onlay urethroplasty and BMG dorsal Inlay urethroplasty provided comparable outcomes for anterior urethral strictures repair. We reported a success rate of 88% in the dorsal onlay group, whereas the success rate in the dorsal inlay group was 86.4%.…”
Section: Discussionsupporting
confidence: 55%
“…First described by the McAninch et al in 1988 [29], urethral ultrasound(UU) to identify stricture has a reported sensitivity of 66% to 100%, specificity of 97% to 98%, and positive and negative predictive values of 50% to 80% and 96% to 98% respectively for anterior stricture 3 to 5 cm long. The usefulness of UU is limited by stricture location as it is more sensitive to stricture in the penile urethra than in bulbar portion [30]. It is also user dependency and the semi-invasive nature of the procedure often requiring local or general anesthesia for full urethra distention.…”
Section: Urethral Stricturementioning
confidence: 99%
“…It has been reported that SUG provides more accurate measurement of stricture length [4,5,6,7,8,9,10], and gives additional information about the depth and density of peri-urethral changes [3,4,5,8] not provided by RUG [11,12], which is helpful when treatment is chosen [13,14,15,16]. In contrast, RUG has been reported to underestimate stricture length [4,5,6,7,8,9,16], and is presumed to be responsible for inappropriate treatment selection and recurrence. More reconstructive surgery was indicated after SUG.…”
Section: Introductionmentioning
confidence: 99%
“…SUG directly identified a stricture by non-compressibility of spongiosum, altered echogenicity and changes in the peri-urethral tissue. Spongiofibrosis appears as hyperechoic [9] or even calcified with stronger reflection zone [3,4]. In 13 patients with long, severe strictures, sonographic contrast medium (200 microparticles/ml; Levovist, Schering, Berlin, Germany) was injected intra-urethrally to help delineate the abnormal lumen from the surrounding tissues and associated abnormalities-secondary lumen, fistulae, reflux into Cowper's glands and abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation